The Form of Javanesse Gamelan in the Worship Liturgy in the Baptism Church Indonesia (GBI) Ngembak - Kristanto, Alfa; Florentinus, Totok Sumaryanto; Sunarto, Sunarto (Catharsis, 2018)
Baptism Church Indonesia (GBI) Ngembak uses Javanesse gamelan (traditional music accompaniment) to accompany the Sundays’ worship which is held every Sunday in the end month. The purpose of this research is to analyze the form of Javanese gamelan music in a worship liturgy of Baptism Church Indonesia (GBI) Ngembak. The research method used qualitative with case study research design. Data collecting techniques are observation, interview, and document study. To maintain its validity, the researcher uses the technique of source triangulation. While the technique of data analysis is done by the process of reduction, presentation, and conclusion (verification). The research findings show that the form of musical composition in one of worship songs in GBI Ngembak is a song titled Puji Nama-Nya (Praise His name) uses bar of 4/4, the types of melody is stepping and jumping. Its harmony is one voice although in the book of Nyanyian Pujian (Hymn) provides the harmony of Soprano, Alto, Tenor, and Bass. The structure of musical form in Puji Nama-Nya song has two parts, they are part A and part B. and the lyrics of this song is a, a , a , a. This song uses a particular musical arrangement of Javanese gamelan accompaniment laras Pelog.